Fabrication of single chamber microbial fuel cell (SMFC) using soil as a substrate - ‪Siti Kudnie Sahari‬; Mohd. Zulhilmi Firdaus Rosli; Amir Maina Butit; Kuryati Kipli; Martin Anyi; Asmahani Awang; Marini Sawawi; Mohamad Rusop Mahmood; Lilik Hasanah; Abdul Rahman Kram; Zaidi Embong; Hafsah Nahrawi (UPM Press, 2022)
This paper presents a Single-chamber Microbial Fuel Cell (SMFC) design by utilizing soil as a substrate with two sets of electrode combinations, which are graphite-activated carbon and copper-zinc of different sizes. It was found that graphite and activated carbon produced greater power density compared to copper and zinc. Moreover, it was observed that the graphite-activated carbon cloth electrode with a bigger surface area of 51cm2 resulted in a higher power density of 904mW/m2. To further improve the voltage production of this model, four SMFCs were stacked in series and connected to a DC-DC boost converter to increase the voltage to 1.482 V for the copper-zinc electrode and 1.722 V for the graphite-activated carbon electrode, respectively, which was sufficient to light up an LED light.